2011
DOI: 10.1002/micr.20892
|View full text |Cite
|
Sign up to set email alerts
|

Autonomization of epigastric flaps in rats

Abstract: The question of how long a flap depends on its pedicle cannot be answered clearly from the available literature. To address this, we investigated the time to flap autonomization in the wound bed and the length of time to the point when flap necrosis is reduced to a clinically negligible level. The superficial epigastric flap was raised in 24 rats. After 3, 5, 7, or 10 days of wound healing, the pedicle was again exposed, ligated, and divided. Values of blood flow (flow), velocity (velocity), hemoglobin level (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…In experimental studies, early signs of capillary blood flow were found in delayed random pattern skin flaps 3–4 days after surgery, and the survival rate of ischemic flaps was increased with local injections of vascular endothelial growth factor 21–24. In a recent experimental study by Mücke et al, it was shown that epigastric flaps in rats develop a 62% necrosis when ligating the pedicle after 3 days, whereas after 5 days, the flaps have almost healed completely 25…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, early signs of capillary blood flow were found in delayed random pattern skin flaps 3–4 days after surgery, and the survival rate of ischemic flaps was increased with local injections of vascular endothelial growth factor 21–24. In a recent experimental study by Mücke et al, it was shown that epigastric flaps in rats develop a 62% necrosis when ligating the pedicle after 3 days, whereas after 5 days, the flaps have almost healed completely 25…”
Section: Discussionmentioning
confidence: 99%
“…The used method in this study (Oxygen to See, O2C, Lea Medizintechnik, Germany) combines lightguide tissue spectrophotometry and laser Doppler flowmetry. Both methods were used separately in a large number of human, and animal studies . The O2C device allows measurements of blood flow (flow) and blood velocity using Doppler flowmetry.…”
mentioning
confidence: 99%
“…On the other hand, clinical reports describe complete flap survival despite early disruption of the pedicle (Chen et al, 2002;Salgado et al, 2002;Wolff et al, 2003Wolff et al, , 2009Wise et al, 2011); this has also been shown in experimental work (Civelek et al, 2009;Mucke et al, 2011). In all three patients, 10e13 days of extracorporeal perfusion were sufficient for bone and muscle tissue, but not for the large skin paddle in patient 1.…”
Section: Discussionmentioning
confidence: 65%